Comparing Representations of 'Self" and "Other" in Iranian and Indian English School Books: A Critical Discourse Analysis - Mojtaba Maghsoudi (Comparative Education Society of Iran ( CESIR), 2020)
English language course books written by local writers are officially prescribed textbooks widely used in Iran and India. Although there is a valuable body of research about these course books, further studies may be needed to comparatively assess their quality as an educational material. This study limits its scope to two textbooks series, namely, the Prospect, and English Standard since both of them are nation-wide textbooks which fully play the roles of course books described in the related literature. The method of analysis was based on a critical discourse analysis framework inspired by Van Dijk's (1998, 2001) socio-cognitive model and Kress and Van Leeuwen's (1996) multi-functional model to facilitate investigation of both textual and meta-textual aspects of the textbooks. The results showed that both textbook series follow similar ideological foundations in terms of promoting a product-based prescriptive and static approach to socio-cultural values through investing on stereotypical "Self" while ignoring otherness. The findings implied that lack of a process-oriented approach to ideological underpinnings of socio-cultural values and codes is a threat to raising inter-cultural understanding in terms of using English as an international language and inter-ethnic awareness of the students who live in multi-ethnic and religiously, culturally, linguistically diverse communities in India and Iran.